Peace, Terrorism, or Civil Conflict? Understanding the Decision of an Opposition Group - Michael Jetter (Institute for the Study of Labor (IZA), 2016)
When do opposition groups decide to mount a terrorism campaign and when do they enter an open civil conflict against the ruling government? This paper models an opposition group's choice between peace, terrorism, and open conflict. Terrorism emerges if executive constraints are intermediate and rents are sizeable. Open conflict is predicted to emerge under poor executive constraints. Analyzing country-level panel data firmly supports these hypotheses, even when relying on within-country variation only in a fixed-effects framework. In particular, both the incidence of terrorism and the likelihood of terrorism onset increase under intermediate executive constraints (following an inverted U-shape) and if large rents are available from natural resources, oil, or foreign development assistance. A one-standard-deviation increase in rents raises casualties by approximately 15 percentage points. Related to civil conflict, moving from an authoritarian regime to comprehensive executive constraints is associated with a decrease in the number of battle-related deaths by approximately 74 percentage points. These findings can help us to better understand and anticipate the underlying decision of opposition groups and their choice between peace, a terrorism campaign, and open conflict.
Keywords: D74; F35; O11; P47; Q34; 330; conflict; executive constraints; foreign aid; natural resource rents; oil rents; political institutions; rents; terrorism